Forgiveness in Vertical Relationships: Incentive and Termination Effects - Vanneste, Bart S.; Frank, Douglas H. (Organization Science, 2014)
Two types of contractual solutions have been proposed for resolving incentive conflicts in vertical relationships: formal and relational (i.e., enforceable or not by third parties). Much is known about the optimal structure of formal contracts, but relatively little is known about the structure of relational contracts. We study a core feature of the latter: the conditions leading to continuation of the relationship, whose prospect gives relational contracts their force. We build a formal model of a vertical relationship between two parties that endogenizes the choice of the minimum performance necessary for continuation as a function of the values of contractibles, noncontractibles, and outside options. The model highlights a basic trade-off between providing strong incentives for the present (incentive effect) and safeguarding relationships for the future (termination effect). The stable relationships that follow from a more forgiving contract are more important under certain conditions (when a lot of value is jointly created by exchange partners, i.e., high contractible value, high noncontractible value, or unattractive outside options); however, strong incentives from a less forgiving contract are more important under other conditions (when a formal contract is insufficient and a relational contract is most important, i.e., high noncontractible relative to contractible value). We discuss implications for the choice of governance of interorganizational relationships.